Transcriptomic decoding of brain function and cerebral blood flow impairments in first-episode drug-naive patients with major depressive disorder - Tu, Miaoqian; Yu, Zelin; Song, Wenwen; Shao, Xiaomei; Xu, Jingjing; Lin, Jiangnan; Xu, Maosheng; Cao, Zhijian (Frontiers in Psychiatry, 2025)
BackgroundMajor depressive disorder (MDD) is highly prevalent and severely impacts daily life. The objective of this study is to investigate the genetic mechanisms behind brain function and perfusion abnormalities, measured by the amplitude of low-frequency fluctuations (ALFF) and cerebral blood flow (CBF) in first-episode drug-naive MDD (FEDN-MDD).MethodsIn this study, we analyzed ALFF and CBF alterations in 34 FEDN-MDD patients and 32 matched healthy controls (HCs) using multimodal magnetic resonance imaging (MRI). Combined with the Allen Human Brain Atlas, we performed spatial correlation analysis between neuroimaging and transcriptomic data, followed by gene enrichment analysis to identify gene expression patterns associated with ALFF and CBF alterations in FEDN-MDD.ResultsCompared to HCs, FEDN-MDD patients exhibited decreased ALFF in the right parahippocampal gyrus, elevated CBF in the right middle frontal gyrus, and reduced CBF in the right superior temporal gyrus. Furthermore, these brain function and perfusion changes were spatially associated with the expression of 1,128 and 1,147 genes, respectively. Importantly, the two gene sets demonstrated both shared and distinct features, primarily related to synaptic plasticity, angiogenesis, and neurovascular coupling (NVC).ConclusionsThese findings highlight the correlation between genetic factors and FEDN-MDD, revealing both shared and distinct molecular associations with brain function and perfusion.